Upaya Meningkatkan Indeks Pembangunan Manusia dengan Pemenuhan Kebutuhan Pokok Mahasiswa UNESA Terdampak Covid-19 - Lucky Rachmawati; Khusnul Fikriyah; Rachma Indrarini; Ladi Watjuba Perdini; Nurul Hanifa (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2021)
The aim of implementing this community service is expected to support government programs in an effort to increase the Human Development Index by Fulfilling the Basic Needs of UNESA Students Affected by Covid-19. The method of implementing activities starts from tracking information affected by Covid-19, identifying partner problems, determining solutions to be offered, implementing PKM activities, monitoring and evaluation, and the final stage is compiling reports. Participants in PKM activities are students receiving basic needs packages of 50 students. The result of this activity is the Fulfillment of the Basic Needs of UNESA Students Affected by Covid-19, of course this activity can support government programs in an effort to increase the Human Development Index.